2018
DOI: 10.1002/mgg3.491
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐590‐3p inhibits trophoblast‐dependent maternal spiral artery remodeling by repressing low‐density lipoprotein receptor‐related protein 6

Abstract: BackgroundThe remodeling of maternal spiral artery following embryo implantation, which relies on well‐regulated trophoblast functions, is a pivotal process to ensure a successful pregnancy. Low‐density lipoprotein receptor‐related protein 6 (LRP6) and microRNAs (miRNAs, miRs) are suggested to be involved in angiogenesis and several vascular diseases; however, their functions in the control of trophoblast remain elusive. We therefore aimed to examine the roles of LRP6 and miR‐590‐3p in the regulation of tropho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…It is well known that LRP6 plays an essential role in the growth and invasion of trophoblasts . Low expression levels of LRP6 inhibited the migration and proliferation of trophoblasts, and several reports demonstrated that LRP6 was highly associated with trophoblast function via the canonical Wnt/β‐catenin pathway . However, whether LRP6 exerts this function through autophagy has never been illustrated until now.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that LRP6 plays an essential role in the growth and invasion of trophoblasts . Low expression levels of LRP6 inhibited the migration and proliferation of trophoblasts, and several reports demonstrated that LRP6 was highly associated with trophoblast function via the canonical Wnt/β‐catenin pathway . However, whether LRP6 exerts this function through autophagy has never been illustrated until now.…”
Section: Introductionmentioning
confidence: 99%
“…LRP6 was reported to be involved in the proliferation, migration and invasion of trophoblast cells via miR-346 [ 28 ]. Notably, miR-590-3p might inhibit trophoblast-dependent maternal spiral artery remodeling by regulating both trophoblast invasion and endovascular formation through the repression of LRP6 [ 29 ]. Based on the results, LRP6 might be regulated by different miRNAs that changing trophoblast function.…”
Section: Discussionmentioning
confidence: 99%
“…MiR‐590‐3p down‐regulated the expressions of MMPs in HTR‐8/SVneo cells through suppressing LRP6 39 . In this present study, the result showed that miR‐95‐5p bind to the 3′ UTR of LRP6, and the expression of miR‐95‐5p was evidently up‐regulated in PE tissues and trophoblast cell lines, suggesting that miR‐95‐5p may be involved in the invasion process of trophoblast cells and affect the occurrence and progress of PE.…”
Section: Discussionmentioning
confidence: 99%